Metabolic Reprogramming in Triple-Negative Breast Cancer - Sun, Xiangyu; Wang, Mozhi; Wang, Mengshen; Yu, Xueting; Guo, Jingyi; Sun, Tie; Li, Xinyan; Yao, Litong; Dong, Haoran; Xu, Yingying (Frontiers in Oncology, 2020)
Metabolic reprogramming is an emerging hallmark of cancer cells, in which cancer cells exhibit distinct metabolic phenotypes to fuel their proliferation and progression. The significant advancements made in the area of metabolic reprogramming make possible new strategies for overcoming malignant cancer, including triple-negative breast cancer. Triple-negative breast cancer is associated with high histologic grade, aggressive phenotype, and poor prognosis. Even though triple-negative breast cancer patients benefit from standard chemotherapy, they still face high recurrence rates and are more likely to develop resistance to chemotherapeutic drugs. Therefore, there is an urgent need to explore vulnerabilities of triple-negative breast cancer and develop novel therapeutic drugs to improve clinical outcomes for triple-negative breast cancer patients. Metabolic reprogramming may provide promising therapeutic targets for the treatment of triple-negative breast cancer. In this paper, we primarily discuss how triple-negative breast cancer cells reprogram their metabolic phenotype and that of stromal cells in the microenvironment to survive under nutrient-poor conditions. Considering that metastasis and chemoresistance are the main contributors to mortality in triple-negative breast cancer patients, we also focus on the role of metabolic adaption in mediating metastasis and chemoresistance of triple-negative breast cancer tumors.